2017
DOI: 10.1556/1646.9.2017.31
|View full text |Cite
|
Sign up to set email alerts
|

Pathomorphological peculiarities of tuberculous meningoencephalitis associated with HIV infection

Abstract: Background and aimsOne of the most severe manifestation displays of tuberculosis (TB) generalization is meningitis/meningoencephalitis. The purpose of this work was to improve the diagnostic efficiency of TB central nervous system (CNS) affection in human immunodeficiency virus (HIV)-infected persons.Materials and methodsMeninges and cerebral tissues, taken from died patients, who were HIV-infected and dead from TB of CNS affection, were investigated histologically.Results and discussionOur examination showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The tissue inflammatory response (number and localization of immune cells) may indicate the outcome of the pathological process caused by various exo-and endogenous factors. (2,3,4,9,23,31,32,33,34,35). During our study, only single T/B-lymphocytes were observed in the mucosa.…”
Section: Discussionmentioning
confidence: 48%
“…The tissue inflammatory response (number and localization of immune cells) may indicate the outcome of the pathological process caused by various exo-and endogenous factors. (2,3,4,9,23,31,32,33,34,35). During our study, only single T/B-lymphocytes were observed in the mucosa.…”
Section: Discussionmentioning
confidence: 48%
“…A total of 3,173 studies were identified in the search, and 58 were included after full text assessment [ 1 , 3 , 7 , 9 17 , 20 22 , 24 , 26 , 30 , 31 , 34 38 , 41 , 44 , 47 54 , 62 64 , 68 – 74 , 77 – 81 , 83 , 86 , 88 90 , 92 , 95 , 97 , 98 ]. The details of the selection process are presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, there are some facts [14] about possibility of the development of immunodeficiency disorder in children, born to women with ALL, that makes impossible to conduct vaccination with live-attenuated vaccines (particularly, tuberculosis, poliomyelitis, etc.) in the first days of life and requires monitoring of the immunological status of children [1719]. Consequently, in case of immunodeficiency, the BCG vaccine strain becomes “paradoxic agent” of opportunistic infection, despite the high quality of national BCG vaccine.…”
Section: Discussionmentioning
confidence: 99%